Dosimetric and radiobiological comparison between conventional and hypofractionated breast treatment plans using the Halcyon system - Tai, Duong Thanh; Phat, Luong Tien; Ngoc Anh, Nguyen; Sang, Huynh Van Tran; Loc, Tran Minh; Hai, Nguyen Xuan; Sandwall, Peter A.; Bradley, David; Chow, James C. L. (Frontiers in Oncology, 2023)
Purpose: The objective of this research is to compare the efficacy of conventional and hypofractionated radiotherapy treatment plans for breast cancer patients, with a specific focus on the unique features of the Halcyon system.Methods and Materials: The study collected and analyzed dose volume histogram (DVH) data for two groups of treatment plans implemented using the Halcyon system. The first group consisted of 19 patients who received conventional fractionated (CF) treatment with a total dose of 50 Gy in 25 fractions, while the second group comprised 9 patients who received hypofractionated (HF) treatment with a total dose of 42.56 Gy in 16 fractions. The DVH data was used to calculate various parameters, including tumor control probability (TCP), normal tissue complication probability (NTCP), and equivalent uniform dose (EUD), using radiobiological models.Results: The results indicated that the CF plan resulted in higher TCP but lower NTCP for the lungs compared to the HF plan. The EUD for the HF plan was approximately 49 Gy (114% of its total dose) while that for the CF plan was around 53 Gy (107% of its total dose).Conclusions: The analysis concludes that while the CF plan is better at controlling tumors, it is not as effective as the HF plan in minimizing side effects. It should be noted that this conclusion has currently been based on treatments obtained with a Halcyon system using the IMRT technique. The study suggests that there may be an optimal configuration for the HF plan that can provide the same or higher EUD than the CF plan, a matter which was not explored in this research.